2016
DOI: 10.1007/s11512-015-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

$R$ -Boundedness versus $\gamma$ -boundedness

Abstract: It is well-known that in Banach spaces with finite cotype, the R-bounded and γ-bounded families of operators coincide. If in addition X is a Banach lattice, then these notions can be expressed as square function estimates. It is also clear that R-boundedness implies γ-boundedness. In this note we show that all other possible inclusions fail. Furthermore, we will prove that R-boundedness is stable under taking adjoints if and only if the underlying space is K-convex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…For Banach function spaces the notion was introduced in [40] under the name R s -boundedness, underlining its connection to the more well-known notion of R-boundedness. An extensive study of ℓ s -boundedness can be found in [24] and for a comparison between ℓ 2 -boundedness and R-boundedness we refer to [25].…”
Section: Preliminariesmentioning
confidence: 99%
“…For Banach function spaces the notion was introduced in [40] under the name R s -boundedness, underlining its connection to the more well-known notion of R-boundedness. An extensive study of ℓ s -boundedness can be found in [24] and for a comparison between ℓ 2 -boundedness and R-boundedness we refer to [25].…”
Section: Preliminariesmentioning
confidence: 99%
“…By replacing the Rademacher random variables in (2.1) by Gaussian variables, one obtains the definition of a γ-bounded collection T ⊆ L(X, Y ). Each R-bounded collection is γ-bounded, and the converse holds if and only if X has finite cotype (see [35,Theorem 1.1]). We choose to work with R-boundedness in this article, both because the notion of R-boundedness is more established and because those stability theorems in this article which use R-boundedness are only of interest on spaces with finite cotype.…”
Section: Preliminariesmentioning
confidence: 99%
“…For a detailed treatment of R-boundedness we refer the reader to [23,29], and for ℓ s -boundedness see [28,50]. For R-and ℓ 2 -boundedness it suffices to consider subsets of T in the defining inequality (see [12,31]). For ℓ s -and ℓ r (ℓ s )-boundedness with r, s = 2 this is not the case: one must consider sequences, allowing for repeated elements.…”
Section: ℓ R (ℓ S )-Boundednessmentioning
confidence: 99%